Form follows function: Morphological and immunohistological insights into epithelial–mesenchymal transition characteristics of tumor buds - Kathrin Enderle-Ammour; Moritz Bader; Theresa Dorothee Ahrens; Kai Franke; Sylvia Timme; Agnes Csanadi; Jens Hoeppner; Birte Kulemann; Jochen Maurer; Philip Reiss; Oliver Schilling; Tobias Keck; et al. (Tumor Biology)
In cancer biology, the architectural concept “form follows function” is reflected by cell morphology, migration, and epithelial–mesenchymal transition protein pattern. In vivo, features of epithelial–mesenchymal transition have been associated with tumor budding, which correlates significantly with patient outcome. Hereby, the majority of tumor buds are not truly detached but still connected to a major tumor mass. For detailed insights into the different tumor bud types and the process of tumor budding, we quantified tumor cells according to histomorphological and immunohistological epithelial–mesenchymal transition characteristics. Three-dimensional reconstruction from adenocarcinomas (pancreatic, colorectal, lung, and ductal breast cancers) was performed as published. Tumor cell morphology and epithelial–mesenchymal transition characteristics (represented by zinc finger E-box-binding homeobox 1 and E-Cadherin) were analyzed qualitatively and quantitatively in a three-dimensional context. Tumor buds were classified into main tumor mass, connected tumor bud, and isolated tumor bud. Cell morphology and epithelial–mesenchymal transition marker expression were assessed for each tumor cell. Epithelial–mesenchymal transition characteristics between isolated tumor bud and connected tumor bud demonstrated no significant differences or trends. Tumor cell count correlated significantly with epithelial–mesenchymal transition and histomorphological characteristics. Regression curve analysis revealed initially a loss of membranous E-Cadherin, followed by expression of cytoplasmic E-Cadherin and subsequent expression of nuclear zinc finger E-box-binding homeobox 1. Morphologic changes followed later in this sequence. Our data demonstrate that connected and isolated tumor buds are equal concerning immunohistochemical epithelial–mesenchymal transition characteristics and histomorphology. Our data also give an insight in the process of tumor budding. While there is a notion that the epithelial–mesenchymal transition zinc finger E-box-binding homeobox 1–E-Cadherin cascade is initiated by zinc finger E-box-binding homeobox 1, our results are contrary and outline other possible pathways influencing the regulation of E-Cadherin.